A theoretical study of the atmospherically important radical–radical reaction BrO + HO2; the product channel O2(a1Δg) + HOBr is formed with the highest rate. Issue 44 (27th October 2016) - Chow, Ronald; Mok, Daniel K. W.; Lee, Edmond P. F.; Dyke, John M.
Abstract : A theoretical study has been made of the BrO + HO2 reaction, a radical–radical reaction which contributes to ozone depletion in the atmosphere via production of HOBr. Abstract : A theoretical study has been made of the BrO + HO2 reaction, a radical–radical reaction which contributes to ozone depletion in the atmosphere via production of HOBr. Reaction enthalpies, activation energies and mechanisms have been determined for five reaction channels. Also rate coefficients have been calculated, in the atmospherically important temperature range 200–400 K, for the two channels with the lowest activation energies, both of which produce HOBr: (R1a) HOBr(X 1 A′) + O2 (X 3 Σ−g) and (R1b) HOBr(X 1 A′) + O2 (a 1 Δg ). The other channels considered are: (R2) BrO + HO2 → HBr + O3, (R3) BrO + HO2 → OBrO + OH and (R4) BrO + HO2 → BrOO + OH. For all channels, geometry optimization and frequency calculations were carried out at the M06-2X/AVDZ level, while relative energies of the stationary points on the reaction surface were improved at a higher level (BD(TQ)/CBS or CCSD(T)/CBS). The computed standard reaction enthalpies (Δ H RX298K) for channels (R1a), (R1b), (R2), (R3) and (R4) are −47.5, −25.0, −4.3, 14.9 and 5.9 kcal mol −1, and the corresponding computed activation energies (Δ E ) are 2.53, −3.07, 11.83, 35.0 and 37.81 kcal mol −1 . These values differ significantly from those obtained in earlier work by Kaltsoyannis and Rowley ( Phys. Chem. Chem. Phys., 2002, 4, 419–427), particularly for channel (R1b), and reasons for this are discussed. In particular, the importance of obtaining an open-shell singlet wavefunction, rather than a closed-shell singlet wavefunction, for the transition state of this channel is emphasized. Rate coefficient calculations from computed potential energy surfaces were made for BrO + HO2 for the first time. Although channel (R1a) is the most exothermic, channel (R1b) has the lowest barrier height, which is negative (at −3.07 kcal mol −1 ). Most rate coefficient calculations were therefore made for (R1b). A two transition state model has been used, involving an outer and an inner transition state. The inner transition state was found to be the major bottleneck of the reaction with the outer transition state having essentially no effect on the overall rate coefficient ( k ) in the temperature range considered. Studying the entropy, enthalpy and free energy of activation of this channel as a function of temperature shows that the main contributor to the magnitude of ln k at a selected temperature is the entropy term (Δ S # / k B ) whereas the temperature dependence of ln k is determined mainly by the enthalpy term (−Δ H # / k B T ). This compares with reactions with positive barrier heights where the enthalpy term makes a bigger contribution to ln k . Comparison of the computed rate coefficients with available experimental values shows that the computed values have a negative temperature dependence, as observed experimentally, but are too low by approximately an order of magnitude at any selected temperature in the range 200–400 K.